2013
DOI: 10.1182/blood-2013-02-482547
|View full text |Cite|
|
Sign up to set email alerts
|

High-resolution HLA matching in hematopoietic stem cell transplantation: a retrospective collaborative analysis

Abstract: Key Points HLA mismatches at the allele and antigen level (possibly with the exception of HLA-DQB1) should be treated equally in donor selection. HLA mismatches at >1 locus (including HLA-DQB1) have additive detrimental effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
156
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(168 citation statements)
references
References 42 publications
3
156
0
9
Order By: Relevance
“…4 The developments of molecular typing technologies and the continuous increase in the number of volunteer donors in the Bone Marrow Donor Worldwide (BMDW) database have undoubtedly improved the identification of well-matched, unrelated donors and contributed to the impressive expansion of HSCT programs worldwide. 1,[4][5][6][7] Over 27 million donors are now registered in the international database (www.bmdw.org) and an increasing proportion of these donors are typed by R ecognition of HLA incompatibilities by the immune system represents a major barrier to allogeneic hematopoietic stem cell transplantation. HLA genotypically identical sibling donors are, therefore, the gold standard for transplantation purposes, but only 30% patients have such a donor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The developments of molecular typing technologies and the continuous increase in the number of volunteer donors in the Bone Marrow Donor Worldwide (BMDW) database have undoubtedly improved the identification of well-matched, unrelated donors and contributed to the impressive expansion of HSCT programs worldwide. 1,[4][5][6][7] Over 27 million donors are now registered in the international database (www.bmdw.org) and an increasing proportion of these donors are typed by R ecognition of HLA incompatibilities by the immune system represents a major barrier to allogeneic hematopoietic stem cell transplantation. HLA genotypically identical sibling donors are, therefore, the gold standard for transplantation purposes, but only 30% patients have such a donor.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, despite these achievements, many patients will still not have a fully matched donor because of the extremely great diversity of HLA alleles and haplotypes. 1,[4][5][6][7] As of January 2016 more than 14,000 HLA alleles have been assigned, accounting for more than 10,000 different HLA proteins (www.ebi.ac.uk/ipd/imgt/hla) ( Figure 1). This increasing level of complexity has negative consequences for patient/unrelated donor matching.…”
Section: Introductionmentioning
confidence: 99%
“…The main requirement for selection of an unrelated donor is well recognized to be one who is a match at 10/10 (or 8/8) HLA alleles. 20,21 Selecting a donor based on secondary selection donor characteristics, such as donor age 22 or other (non-classic HLA) genetic factors, [23][24][25] can further enhance outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the disparity of HLA molecules in HLA antigen mismatch is greater than that in HLA allele mismatch without HLA antigen mismatch, the impact of HLA mismatch on the clinical outcome for antigen mismatch was considered to be, for practical purposes, similar to that for allele mismatch, as reported previously in the setting of unrelated HSCT [4,7,8]. Although the impact of an HLA mismatch at each locus varied among the studies, there is a consensus that an HLA mismatch at any locus, including A, B, C and DRB1, is in general associated with a poor clinical outcome [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 95%
“…In terms of HLA mismatch in the setting of unrelated hematopoietic stem cell transplantation (HSCT), previous studies have shown that high-resolution HLA mismatch significantly affected the clinical outcome [1,2]. Several retrospective studies have demonstrated that the presence of HLA allele mismatch was associated with an increased risk of graft-versus-host disease (GVHD) in unrelated HSCT [3][4][5][6]. Although the disparity of HLA molecules in HLA antigen mismatch is greater than that in HLA allele mismatch without HLA antigen mismatch, the impact of HLA mismatch on the clinical outcome for antigen mismatch was considered to be, for practical purposes, similar to that for allele mismatch, as reported previously in the setting of unrelated HSCT [4,7,8].…”
Section: Introductionmentioning
confidence: 99%